Karakteristik Sensori, Nilai pH, dan Aktivitas Antioksidan Minuman Kefir Fungsional Berbahan Susu Sapi dan Madu Clover (Trifolium spp.): Sensory Characteristics, pH Value, and Antioxidant Activity of Functional Kefir Beverage Made from Cow’s Milk and Clover Honey (Trifolium spp.) - Astrid Noviana; Prima Novitasari; Amalia An Nidha; Rifqoh Muhlihah Baehaki; Egidea Nada Afifa; Dhiya Fauziyyah; Alaina Atsabita (Amerta Nutrition, 2025)
Background: Kefir is a fermented milk product that contains antioxidants capable of enhancing physical performance by supporting the immune system, digestion, and reducing oxidative stress. However, kefir is less accepted by some individuals due to its high acidity. Clover honey possesses a distinctive flavor that can improve the taste of food products. Objectives: This study aims to identify the sensory characteristics and evaluate the pH value and antioxidant activity of kefir beverages made from cow's milk and clover honey. Methods: Sensory evaluation of kefir beverages with varying ratios of cow's milk to clover honey of 90%:10% (KMH1), 85%:15% (KMH2), 80%:20% (KMH3), and 75%:25% (KMH4) was conducted by eight trained panelists using the Quantitative Descriptive Analysis (QDA) method and preference tests. The pH value was determined using a pH meter, and antioxidant activity was assessed using the 1,1-diphenyl-2-picrylhydrazyl (DPPH) method.  Results: A total of 38 sensory attributes were identified. KMH2 and KMH3 ranked first based on the preference test (score=0.5225). They exhibited sour taste intensity scores of 7.88±1.13 and 5.63±1.60, respectively, and sweet taste intensity scores of 4.50±2.07 and 7.00±1.69, respectively. The pH values of all samples ranged from 4.15 to 4.47, which is within the normal pH range for kefir products. No significant differences were observed in the antioxidant activity across all formulations, with IC50 values ranging from 19.09 to 25.38, indicating very strong activity (p-value=0.223).  Conclusions: Kefir beverages made from cow's milk and clover honey exhibit favorable sensory characteristics, appropriate pH values, and very strong antioxidant activity, suggesting their potential use as functional food to enhance physical performance.